Early onset of action with a 17β-estradiol, softgel, vaginal insert for treating vulvar and vaginal atrophy and moderate to severe dyspareunia. Issue 11 (November 2019) - Constantine, Ginger; Millheiser, Leah S.; Kaunitz, Andrew M.; Parish, Sharon J.; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: The softgel 17β-estradiol (E2) vaginal inserts (4 and 10 μg; Imvexxy; TherapeuticsMD, Boca Raton, FL) are FDA approved for treating moderate to severe dyspareunia associated with postmenopausal vulvar and vaginal atrophy (VVA). The objective here was to determine responder rates at week 2 and whether week-2 findings predicted week-12 responders in the REJOICE trial. Methods: Postmenopausal women received E2 vaginal inserts 4, 10, or 25 μg, or placebo for 12 weeks. Proportion of responders (having ≥2 of the following: vaginal superficial cells >5%, vaginal pH <5.0, or dyspareunia improvement of ≥1 category) were calculated. Odds ratios (ORs) for positive response at week 12 given a positive response at week 2 were determined in the efficacy evaluable (EE) population. Results: The responder rate (in EE population [ n = 695]) was 74% to 82% with E2 inserts versus 24% with placebo at week 2, and 72% to 80% versus 33% at week 12. Positive treatment responses were 9- to 14-fold higher with vaginal E2 than with placebo at week 2, and 5- to 8-fold higher at week 12. Response at week 2 predicted response at week 12 in the total population (OR 13.1; 95% CI, 8.8-19.7) and with active treatment only (OR 7.9; 95% CI, 4.7-13.2). Conclusions: A high percentage of postmenopausal women with moderate to severe dyspareunia responded with the E2 softgel vaginal insert at week 2, and a positive response at week 2 predicted a positive response at week 12.